Preparation and characterisation of poly (vinyl alcohol)/chitosan/silicon dioxide (PVA/CS/SiO2) beads for the chromium (VI) (Cr(VI) removal - Sulaiman, Syazwan Liyana (2016)
Chromium pollution has become a global issue and many techniques have been developed for the removal of Chromium (VI) (Cr(VI)) from wastewater. In this study, blend polymer absorbent beads which was poly (vinyl alcohol)/chitosan/silicon dioxide (PVA/CS/SiO2) beads were prepared by dropwise method by crosslinking with sodium hydroxide and ethanol and further crosslinked with glutraldehyde for the purpose of Cr(VI) ion removal in aqueous solution under UV irradiation. All of the samples of PVA/CS/SiO2 beads were put under UV irradiation for two hours in the high acidic medium of Cr(VI) solution. After that, the Cr solution was analysed by atomic absorption spectroscopy (AAS), and the beads have been characterised by scanning electron microscopy (SEM), energy dispersive x-ray spectroscopy (EDX) and fourier transform infrared spectroscopy (FTIR) analysis. pH value for each sample before and after the absorption test also has been measured. As a result, the data obtained by AAS showed that the Cr(VI) solution of PVA/CS/SiO2 beads of PCS 25 recorded the most percentage of Cr(VI) absorption which was 99.9% meanwhile PCS 1 recorded the less percentage of Cr(VI) absorption which was 93.4%. Beads morphology images showed that all of the 25 samples of PVA/CS/SiO2 beads revealed macro and micro pores on the surface of beads before the Cr(VI) absorption and the pore size increased with the increment of CS and SiO2 concentration. The pores for all of the sample beads before the Cr absorption can be clearly seen. However, the surface of beads became smooth after Cr(VI) absorption, indicating that the pores on the surface were filled up with Cr. This change was further supported by EDX analysis which provided the existence of Cr peaks as the direct evidence. Whereas, FTIR results showed small shifts in wavelength at several peaks before and after the Cr absorption for each sample indicated that there was metal binding process taking place at the surface of the beads. The results of pH value of Cr after the absorption test showed that PCS 1 recorded the lowest pH value which was 5.81 and PCS 25 recorded the highest pH value which was 6.08. As for the conclusion, PCS 25 has been chosen as the best absorbent with the highest Cr absorption and the results suggested that, the use of PVA/CS/SiO2 beads is a sustainable strategy for eliminating Cr(VI) from industrial wastewater.